GURU PAHLAWAN TANPA TANDA JASA - B, Muhammad Rusmin (Universitas Islam Negeri Alauddin Makassar, 2019)
Teachers are professions that require special expertise. This profession cannot be practiced by every human being. People who are good at talking in certain fields, can not be called a teacher. To become a teacher requires special conditions. Being a professional teacher must truly master the ins and outs of education and teaching complemented by a variety of other sciences. This is what needs to be fostered and developed through a certain period of education or pre-service education.